The Role of Information Systems in Student Organizations at Satya Wacana Christian University - Delano, Theofan; Chernovita, Hanna Prillysca (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Information systems have become an integral component in supporting the operations of student organizations at Satya Wacana Christian University (UKSW). These systems are designed to streamline data management, enhance communication, and improve operational efficiency, ultimately supporting academic and extracurricular activities. Despite their potential, the implementation of information systems in student organizations faces challenges, including technical limitations and resistance to change. This qualitative study employed a case study approach to explore the role, supporting factors, and challenges of information systems in student organizations at UKSW. Data were collected through in-depth interviews with three student leaders, document analysis, and observation. A thematic analysis method was used to categorize and interpret the data, providing a comprehensive understanding of the system's impact and areas for improvement. The findings reveal that information systems significantly improve the efficiency of data management, event coordination, and communication among student organizations. Centralized data systems facilitate task distribution and enhance transparency and accountability. However, challenges such as technical limitations among students, system bugs, and inconsistent updates hinder optimal utilization. Strong institutional support, active student involvement, and continuous training were identified as critical enablers of successful implementation. The study highlights the need for improvements in user training, technical support, and system interactivity to overcome challenges and maximize the benefits of information systems. Recommendations include increasing system user-friendliness, ensuring regular updates, and fostering collaboration between IT teams and student organizations. These steps are crucial for enhancing system adoption, engagement, and overall effectiveness.